2017
DOI: 10.1007/s12291-017-0654-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Preanalytical Quality Indicators by Six Sigma and Pareto`s Principle

Abstract: Preanalytical steps are the major sources of error in clinical laboratory. The analytical errors can be corrected by quality control procedures but there is a need for stringent quality checks in preanalytical area as these processes are done outside the laboratory. Sigma value depicts the performance of laboratory and its quality measures. Hence in the present study six sigma and Pareto principle was applied to preanalytical quality indicators to evaluate the clinical biochemistry laboratory performance. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…In mathematical fields, sigma is the symbol for standard deviation (SD) . Some studies have shown that sigma metrics can be applied to quantitatively evaluate errors or defects in testing projects in clinical laboratories, and the results are quantified as defects per million (DPMs) . The Six Sigma metric corresponds to 3.4 DPM opportunities in a clinical process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mathematical fields, sigma is the symbol for standard deviation (SD) . Some studies have shown that sigma metrics can be applied to quantitatively evaluate errors or defects in testing projects in clinical laboratories, and the results are quantified as defects per million (DPMs) . The Six Sigma metric corresponds to 3.4 DPM opportunities in a clinical process.…”
Section: Introductionmentioning
confidence: 99%
“…The Six Sigma metric corresponds to 3.4 DPM opportunities in a clinical process. To date, sigma methodology has mainly been applied in pre‐analytical and analytical processes in clinical laboratories, focusing on the evaluation of biochemical and immunoassay tests …”
Section: Introductionmentioning
confidence: 99%
“…So far, the sigma methodology has mainly been applied in the evaluation of immunoassay and biochemical tests. 4,5 In this study, Westgard sigma rules with a run size management method were used to evaluate the detection performance of clinical test items in a biochemical laboratory with the objectives of improving the quality level of the clinical biochemical laboratory and reducing the risk to patients.…”
mentioning
confidence: 99%
“…Berdasarkan hasil penelitian yang dilakukan, responden berumur 35-40 tahun dan >40 tahun yang dikategorikan sebagai perawat memiliki pengetahuan yang kurang terkait pengelolaan bahan habis pakai, yang dapat dikategorikan sebagai umur yang sudah tidak lagi fokus terhadap berbagai pekerjaan yang menuntutnya. Menurut Kulkarni et al (2018) , pengetahuan dan minat perawat yang telah diberikan sosialisasi akan berpengaruh kepada pekerjaan, penggunaan alat medis yang prioritas, pembukuan yang lebih rapi, sehingga memberikan keuntungan finansial kepada rumah sakit.…”
Section: B Pembahasanunclassified